High temperature absorbing coatings with excellent performance combined Al2O3 and TiC material. Issue 5 (May 2020) - Shao, Tengqiang; Ma, Hua; Wang, Jun; Feng, Mingde; Yan, Mingbao; Wang, Jiafu; Yang, Zhaoning; Zhou, Qian; Luo, Heng; Qu, Shaobo
Abstract: A series of challenges are impeding the development of high temperature electromagnetic (EM) wave absorbing materials in x band. In this study, to deal with this problem, a coating, (1-x).wtAl2 O3 ∼x.wtTiC, is designed and prepared using plasma spraying technology. Its permittivity increases with temperature and TiC content, which endows it with a good EM impedance at high temperature. The coating possesses excellent EM absorbing performance at 800 ℃. When the x value equals 0.2 and thickness 1.6 mm, the coating exhibits an EAB of 3.45 GHz at 800℃, and a reflection loss lower than -8 dB in whole x band. The XRD result shows that only two phases exist in the coating. The SEM images illustrate that TiC is unevenly dispersed in Al2 O3, causing loss of conductivity and interface polarization. The finding not only broadens the application of TiC-based materials but also indicates the promising future of this material system.